A Model to Assess the Probabilities of Growth, Fiscal, and Financial Crises - Basu, Suman (IMF Working Papers; Working Paper ;, 2017)
This paper summarizes a suite of early warning models to assess the probabilities of growth, fiscal, and financial crises in advanced economies and emerging markets. We estimate separate signal-extraction models for each type of crisis and sample of countries, and we use our results to generate 'histories of vulnerabilities' for countries, regions, and the world. For the global financial crisis, our models report that vulnerabilities in advanced economies were rooted in the bursting of leveraged bubbles, while vulnerabilities in emerging markets stemmed from lengthy booms in credit and asset prices combined with growing weaknesses in the corporate and external sectors.